Perancangan Interior One Stop Mother and Baby Care di Surabaya - Elvina Theresia; Adi Santosa; Poppy Firtatwentyna Nilasari (Intra, 2019)
Every department store sells a variety of products for both men and women of all ages including those with special needs such as pregnant women. In Surabaya there is no department store that provides all the needs for pregnant and lactating mothers. To facilitate pregnant and lactating mother, a department store is made to provide various facilities such as gym, spa, café and lounge, as well as products for pregnant and lactating mothers. All these facilities are adjusted to the needs of pregnant and lactating mothers based on literature and research. Brainstorming was also done out with the aim of maximize design results from all aspects that can affect pregnant and lactating mothers. With the existence of the department store, it can make it easier for pregnant and lactating mothers to fulfil all their needs efficiently on both for service and product needs. With this design project, pregnant and lactating mothers in Surabaya no longer have to bother to move around stores, so it becomes more efficient and will not exhaust them.